Solid State Synthesis of Silver Nanoparticles Using Violuric Acid as a Novel Reducing Agent - Ahmad, Amir Abdulrahman (Science Journal of University of Zakho, 2022)
Metal Nanoparticles (NPs) are recognized as the most attractive materials due to their distinct physical and chemical characteristics. Several physical and chemical synthesis methods have already been tested to obtain NPs of appropriate size and shape. Although the chemical-based solution methods provide NPs within a proper size and shape and can be reasonably controlled, they require a large amount of raw material including solvents, capping agents, etc., which usually lead to toxic output and waste. In this study, the author tested an easy and environmentally friendly solid-state synthesis pathway for synthesizing silver (Ag) NPs within a suitable size and shape, using a novel reducing agent. Silver carbonate (Ag2CO3) was allowed to react with Violuric acid (C4H3N3O4) as a reducing agent through a solid-state grinding method for one hour. The results confirmed that Violuric Acid can be considered a promising reducing agent that results in the formation of well-shaped spherical Ag NPs within an average particle size of about 60 nm.